Dry Eye Syndrome in Refractive Patients. Literature Review - A. V. Doga; S. A. Borzenok; I. A. Mushkova; A. N. Karimova; M. R. Obraztsova; M. Kh. Khubetsova; D. S. Ostrovskiy (Oftalʹmologiâ)
Dry eye syndrome is a multifactorial disease of the ocular surface, which is based on the development of hyperosmolarity, inflammation and sensorineural disorders in the imbalance of the structural components of the tear film. The main complaints of refractive patients after keratorefractive surgery are a feeling of dryness in the eyes, a foreign body, redness, blurring of the image, which is due to the clinical manifestations of post-refractive dry eye syndrome. There are factors that contribute to the development of postrefractive dry eye syndrome, such as: neurotrophic epitheliopathy, postoperative inflammation, damage to goblet cells, toxic corneal epitheliopathy caused by preservatives contained in eye drops, leading to inadequate restoration of the tear film. In clinical practice, to assess the stability of the tear film, a method is used to determine the tear film rupture time using invasive and non-invasive methods. Invasive methods include: staining of the ocular surface with a solution of fluorescein during the Norn test. To date, laboratory diagnostics expands the understanding of the pathogenesis, etiology and mechanisms underlying the xerosis of the ocular surface at the molecular level, and also facilitates the diagnosis and prognosis of dry eye syndrome. Laboratory methods of the ocular surface include the study of biomarkers of lacrimal fluid, conducting impression cytology with an assessment of the condition of goblet cells. In this regard, it is necessary to have a deep understanding of the main etiopathogenetic links of dry eye syndrome, a wide range of diagnostics of the condition of the ocular surface before and after the surgical stage of patient management, which will determine the success of keratorefractive surgery and a stable course of the postoperative period.